The Cultural Forces and Women Livelihood Options in Rural Areas of Kano State, Nigeria - Lambu, Ibrahim Badamasi (Advances in Social Sciences Research Journal, 2016)
The paper explores the cultural issues surrounding buying and selling engaged by rural women to supplement their housewifery functions. The aim of the study is to evaluate the various livelihood options that are culturally permissible in the study area with a view to understand the variation of occupations in relation to the cultural norms of the people involved. Occupational clusters were identified; the reasons for adoption of occupations, risks and inconveniences as well as people responses were envisaged. It is cross sectional research that involves both quantitative and qualitative type of data. Demographic characteristics of women especially age and preferences were captured. Questionnaires and interviews were employed for the quantitative and qualitative data collection respectively. The study discovered that indoor occupations such as food and eatery items within matrimonial homes are the modal livelihood options due to cultural values. Problem of poverty affects women due to social inequality and the people who patronize such occupations in the rural environment are affected by poverty. Some respondents described the women’s occupation as a ‘last option’ because the profit obtainable is too meager commensurate to the laboring nature of the occupations. Many people described the act as marginal due to hardship, burden and risk involve. Many women sustain injury; at times enter social trauma in the livelihood options. The women complain of poor economic backing and support from husbands, relatives and family members. High cost of materials in some of women’s occupations affect the choice of the occupation to pursue. The study pathetically discovered that the women are marginalized due to lack of capital. The loitering under the sun and rain is affecting their health (mental and moral) hence at high risk of ailment. The study recommends for provision of financial and moral supports by both government and Non-Governmental Organizations (NGOs) to reduce the burden on women who are for various cultural reasons made poor so that they are allow to earn living with minimum duress